Gratitude of Generation Z in the Context of Javanese Culture: is 'Nrimo Ing Pandum' Still Relevant? - Sitepu, Meilya Anggara S; Nurhayati, Siti Rohmah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Generation Z is entangled in prestige and the FOMO (Fear of Missing Out) phenomenon due to lifestyle and social interactions. Generation Z has a relatively wasteful financial situation that impacts other financial problems, especially as they work in Yogyakarta—one of the poorest cities in Indonesia with the second highest expenditure in Java. This raises concern over their psychological and financial well-being. The urgency of this study lies in the need to understand how internal psychological resources such as gratitude, rooted in cultural values like nrimo ing pandum (Javanese acceptance), can help Generation Z navigate economic pressures and lifestyle demands. Amidst modernization and consumerism, traditional values are at risk of being eroded, making it essential to explore how such values are interpreted and lived today. This study aims to explore the picture of gratitude of Generation Z who work in Yogyakarta in the context of Javanese culture nrimo ing pandum. This study combines phenomenological methodology with a qualitative approach. In-depth interviews and observations were conducted with five Generation Z employees working in Yogyakarta. Thematic analysis is the analysis method used in this study. The results found that Generation Z workers have demonstrated patience and gratitude, but a lack of nrimo (acceptance), due to a reckless attitude shaped by the pursuit of prestige and FOMO-driven consumptive behavior.